Исследование применимости матрицы смежности для выявления стеганоаудиоконтейнеров - Кошкина, Н.В (Проблемы управления и информатики, 2014)
Досліджено чутливість рядків матриць суміжності аудіосигналів, обчислених в часовій області та області вейвлет-коефіцієнтів, до послідовного та розподіленого стеганографічних вкраплень за методом НЗБ. Виявлено залежності між наповненістю аудіоконтейнерів та точністю їх SVM-класифікації за особливостями рядків матриць суміжності. Запропоновано спосіб визначення довжини прихованого повідомлення шляхом зваженого голосування сукупності бінарних класифікаторів, що розрізняють стеганоконтейнери двох різних наповненостей. The sensitivity of rows of the co-occurrence matrix of audio signals that were computed in the time and the wavelet coefficients domains to distributed and sequential steganographic embedding by LSB method has been investigated. The relations between the steganographic capacity and the accuracy of SVM classification based on rows features of co-occurrence matrices stego- and normal audios were found. The method for determination of the length of hidden messages by weighted voting of binary classifiers set, that distinguish between two stego audios with different steganographic capacity has been proposed.